(untitled) (European Journal of Marketing and Economics, 2022)
The new communication tool of our current era is certainly Facebook because it is the most commonly used social network application in the world. Therefore, consumers perceive businesses which are not a member of Facebook as a business which cannot keep up with the new era and thus they want their favourite brands to be on Facebook. However, for businesses to be on Facebook is not just about opening a profile page. Businesses need to create a brand community that they get into interaction with their stakeholders in order to gain dynamism and mobility to their Facebook brand fan pages. Therefore, businesses need a variety of effective corporate communication strategies that they can apply on their Facebook pages. The corporate communication strategy that a business employs on Facebook should be compatible with the goals and purposes that a business wants to reach. A business which use a certain corporate communication strategy on Facebook will determine the contents that it will share on Facebook in line with this strategy and will create the desired perception on its target audience. On the other hand, a business which doesn’t apply a particular corporate communication strategy on Facebook probably doesn’t know which goals that it wants to reach. Therefore, businesses which share random contents on their Facebook pages try to continue their Facebook pages by trial and error. However, because of this situation, they cannot get the desired effectiveness, appeal and efficiency from their Facebook pages in the long term. Furthermore, stakeholders need some level of motivation in order to follow businesses on Facebook. If a business knows what the motives of usage are, it can shape its Facebook messages in the right direction. This way, more followers will gather around the brand community of the business on Facebook.